The effectiveness of FX interventions: A meta-analysis - Lucía Arango-Lozano; Lukas Menkhoff; Daniela Rodríguez-Novoa; Mauricio Villamizar (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
There is ample empirical literature centering on the effectiveness of foreign exchange intervention (FXI). Given the mix of objectives and country-heterogeneity, the general lack of consensus thus far is no surprise. We shed light on this debate by conducting the first comprehensive meta-analysis in the FXI literature, with 279 reported effects that stem from 74 distinct empirical studies. We cover estimations conducted in 19 countries across five decades. Overall, our meta-survey reports an average depreciation of domestic currency of 1% and a reduction of exchange rate volatility of 0.6%, in response to a 1 billion US dollar purchase. Results are qualitatively confirmed but smaller in size under fixed and random-effect estimations. When narrowing in on different economic factors, we find that effects are magnified for cases consistent with the monetary trilemma (greater if financial openness and monetary independence are low). Effects are also larger in emerging than advanced economies, when banking crises remain mild, and when interventions are large in size and are announced.
Keywords: C83; E58; F31; 330; foreign exchange intervention; exchange rate; meta-analysis